Blue and Black Ballpoint Pen Inks: a Systematic Review for Ink Characterization and Dating Analysis - Roberta Petry Gorziza (2019)
Documents are frequent targets of fraud and adulteration. Sometimes it is not enough to determine the document’s authenticity or authorship, but it is also necessary to demonstrate when the document was signed or written. Determining the age of a document, also known as ink dating analysis, is still a challenge for the forensic examiners. There are two main approaches for the dating of ballpoint pen inks: the static method, which is based on the characterization and identification of the ink composition and comparison to a reference collection, and the dynamic method, which involves the study of ink’s processes and alterations that occur with time, considering environmental aging factors such as light and humidity. This article aims to provide a comprehensive systematic review of the studies regarding ballpoint ink characterization and dating, in the last ten years. There are several methods, destructive and non-destructive, which are capable of characterizing and differentiating blue and black ballpoint pens that have shown applicability to the static approach. Regarding the dynamic dating methods, most studies quantified the loss of 2-phenoxyethanol (2-PE) solvent over time using GC-MS, or studied the dyes degradation through different methods. Although ink dating approaches offer relatively good accuracy, there is still more research to be done, such as the documents’ storage conditions evaluation, the influence of initial ink quantity variation between different pen brands and writing fists, and the type of paper.